Evolutionary rate variation among genes involved in galactomannan biosynthesis in Coffea canephora. Issue 5 (11th February 2020) - Ogutu, Collins; Cherono, Sylvia; Ntini, Charmaine; Mollah, Mohammad Dulal; Zhao, Lei; Belal, Mohammad A.; Han, Yuepeng
Abstract: The endosperm cell walls of mature coffee seeds accumulate large amounts of mannan storage polysaccharides, which serve as nutrient reserve for embryo and contribute to beverage quality. Our study investigated the evolutionary patterns of key galactomannan (GM) biosynthesis genes using d N / d S ratio, synteny, and phylogenetic analysis and detected heterogeneity in rate of evolution among gene copies. Selection ratio index revealed evidence of positive selection in the branch editing gene Coffea canephora alpha (α) galactosidase ( Cc‐alpha Gal ) at Cc11_g15950 copy ( ω = 1.12), whereas strong purifying selection on deleterious mutations was observed in the Coffea canephora uridine diphosphate (UDP)‐glucose 4′‐epimerase ( Cc‐UG4E ) and Coffea canephora mannose‐1P guanylytransferase ( Cc‐MGT ) genes controlling the crucial nucleotide carbon sugar building blocks flux in the pathway. Relatively low sequence diversity and strong syntenic linkages were detected in all GM pathway genes except in Cc‐alpha Gal, which suggests a correlation between selection pressure and nucleotide diversity or synteny analysis. In addition, phylogenetic analysis revealed independent evolution or expansion of GM pathway genes in different plant species, with no obvious inferable clustering patterns according to either gene family or congruent with evolutionary plants lineages tested due to high dynamic nature and specific biochemical cell wall modification requirements. Altogether, our study shows a significant high rate of evolutionary variation among GM pathway genes in the diploid C. canephora and demonstrates the inherent variation in evolution of gene copies and their potential role in understanding selection rates in a homogenously connected metabolic pathway. Abstract : This study investigated the evolutionary patterns of key galactomannan biosynthesis genes using selection ratio index, synteny, and phylogenetic analysis and detected heterogeneity in rate of evolution among gene copies.